Peningkatan Hasil Belajar IPAS Siswa Menggunakan Pembelajaran Kooperatif Tipe TGT Berbantuan Educaplay Kelas VI SDN Jajar Tunggal III Surabaya - Firdha Rosavina Putri; Desi Eka Pratiwi; Endang Sulistiya Wati (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the effectiveness of applying the cooperative learning model of the TGT type with the aid of Educaplay in improving students' learning outcomes in the IPAS subject. This Classroom Action Research (CAR) was conducted at SDN Jajar Tunggal III Surabaya. The learning outcomes of the IPAS topic on Diseases Affecting the Musculoskeletal System during the pre-cycle, cycle I, and cycle II showed a significant improvement. In the pre-cycle, the mastery achieved was only 29%, with 8 students reaching mastery and 20 students not yet achieving it. In cycle I, the percentage of students reaching mastery rose to 61%, with 17 students achieving mastery and 11 students still not reaching it. In cycle II, the percentage of students achieving mastery soared to 86%. These data indicate that both cycles successfully improved students' learning outcomes by applying the TGT cooperative learning model with the help of Educaplay.